STILT transport model results (footprints) for station SVB035 in 2019 - Christoph Gerbig; Ute Karstens; Frank-Thomas Koch (Integrated Carbon Observation System, 2022)
STILT footprints for a European station location. The Stochastic Time Inverted Lagrangian Transport (STILT) model (Lin et al., 2003, https://doi.org/10.1029/2002JD003161) was driven by ECMWF-IFS meteorological analysis. Footprints were aggregate over 10 days backward in time to provide an overview of the region of influence. Footprints were produced using the STILT Footprint Tool at ICOS Carbon Portal (https://www.icos-cp.eu/data-services/tools/stilt-footprint) based on the STILT model code available at https://stilt-model.org/index.php/Main/HomePage.
The STILT results are also visualized at https://stilt.icos-cp.eu/viewer/?stationId=SVB035&fromDate=2019-01-01&toDate=2019-12-31
Gerbig, C., Karstens, U., Koch, F. (2022). STILT transport model results (footprints) for station SVB035 in 2019, 2019-01-01–2019-12-31, ICOS RI, https://hdl.handle.net/11676/vJWbb7V0crxGLJkxUCpzbVVM
Keywords: Carbon Portal; ICOS; atmospheric model; transport model footprint; transport model footprint; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap